After collapse : the regeneration of complex societies - Nichols, John J. (John Jackson), 1963-; Schwartz, Glenn M. (University of Arizona Press, 2010)
From the Euphrates Valley to the southern Peruvian Andes, early complex societies have risen and fallen, but in some cases they have also been reborn. Prior archaeological investigation of these societies has focused primarily on emergence and collapse. This is the first book-length work to examine the question of how and why early complex urban societies reappeared after periods of decentralization and collapse. Ranging widely across the Near East, the Aegean, East Asia, Mesoamerica, and the Andes, these cross-cultural studies expand our understanding of social evolution by examining how societies were transformed during the period of radical change now termed "collapse." They seek to discover how societal complexity reemerged, how second-generation states formed, and how these re-emergent states resembled or differed from the complex societies that preceded them. The contributors draw on material culture as well as textual and ethnohistoric data to consider such factors as preexistent institutions, structures, and ideologies that are influential in regeneration; economic and political resilience; the role of social mobility, marginal groups, and peripheries; and ethnic change. In addition to presenting a number of theoretical viewpoints, the contributors propose reasons why regeneration sometimes does not occur after collapse. A concluding contribution by Norman Yoffee provides a critical exegesis of "collapse" and highlights important patterns found in the case histories related to peripheral regions and secondary elites, and to the ideology of statecraft. After Collapse blazes new research trails in both archaeology and the study of social change, demonstrating that the archaeological record often offers more clues to the "dark ages" that precede regeneration than do text-based studies. It opens up a new window on the past by shifting the focus away from the rise and fall of ancient civilizations to their often more telling fall and rise